Learning Using an Open Approach to Improve Creative Thinking Skills in Solving Mathematical Problems on Field Structure Materials - Hari Sugiharto Setyaedhi; Fajar Arianto; Husni Mubarok (Universitas Pendidikan Ganesha, 2025)
The main problem in mathematics learning is the low level of students’ creative thinking skills, as indicated by difficulties in understanding concepts, solving contextual problems, and the limited ability to generate various alternative solutions. This study aims to examine the effectiveness of the open-ended approach in improving students’ mathematical creative thinking skills, particularly in geometry. The subjects of the study were 50 secondary school students divided into experimental and control classes. The research method used was a quasi-experiment with a pretest-posttest control group design. Data collection techniques included open-ended essay tests developed based on creative thinking indicators, observation, and documentation. Data analysis was carried out using the N-Gain test to determine learning improvement and inferential statistical tests to examine the significance of differences between groups. The results showed that the experimental class using the open-ended approach obtained an average N-Gain score of 72.13 (high category), while the control class only achieved 20.52 (low category). These findings demonstrate that the open-ended approach is effective in enhancing students’ mathematical creative thinking skills, particularly in the aspects of fluency and flexibility, although originality and elaboration still require further attention.